Publisher Correction: Fuelling conditions at staging sites can mitigate Arctic warming effects in a migratory bird. Issue 1 (December 2018) - Rakhimberdiev, Eldar; Duijns, Sjoerd; Karagicheva, Julia; Camphuysen, Cornelis; Dekinga, Anne; Dekker, Rob; Gavrilov, Anatoly; Horn, Job; Jukema, Joop; Saveliev, Anatoly; Soloviev, Mikhail; Tibbitts, T.; et al.
In the original HTML version of this Article, the order of authors within the author list was incorrect. The consortium VRS Castricum was incorrectly listed after Theunis Piersma and should have been listed after Cornelis J. Camphuysen. This error has been corrected in the HTML version of the Article; the PDF version was correct at the time of publication.